Mechanical properties and failure law of composite rock containing two coplanar fractures - Yuan, Hao; Xiao, Taoli; She, Haicheng; Zheng, Yuanlong; Chen, Xiang (Frontiers in Earth Science, 2023)
Composite rocks comprise common rock structures used in geotechnical engineering. The fracture configuration has a significant influence on the mechanical behavior, failure mode, and crack propagation of the composite rock. In this study, a composite rock with two prefabricated coplanar fractures was considered. Combined with laboratory uniaxial compression tests and digital image acquisition systems, the effects of different fracture lengths and inclination angles on the mechanical properties and failure characteristics of rocks were systematically studied. The following results were obtained: (1) During the process of loading deformation of the rock sample, the peak stress and elastic modulus increased with an increase in the fracture inclination angle and decreased with an increase in the fracture length. The deterioration coefficient k decreased with an increase in the fracture inclination angle and increased with an increase in the fracture length. (2) The failure mode of the rock samples was mainly controlled by the fracture inclination angle and the material of the two types of rocks, and the fragmentation degree was mainly controlled by the fracture length. With an increase in the fracture inclination angle, the rock sample exhibited the change rule of ‘double Y’ type → ‘double Z’ type → ‘Z’ type failure. (3) The coalescence mode of the rock bridge was controlled by the fracture inclination angle and the structural plane. By defining four types of rock bridge coalescence modes, it was found that the larger the fracture inclination angle, the easier it was for the rock bridge to coalesce. When the fracture inclination angle increased to 90°, the rock bridge no longer coalesced, and the structural plane inhibited the coalescence of the rock bridge. (4) The cracks generated at four time points were defined, and it was found that the positions of the cracks were mainly affected by the length of the fracture.. (5) At a low fracture inclination angle (α ≤ 30°), the crack propagation had obvious aggregation band formation. Above moderate fracture inclination angles (α > 30°), the crack aggregation band gradually weakened and expanded in the direction of dispersion.